2006
DOI: 10.1111/j.1525-1497.2006.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of interest disclosure policies and practices in peer-reviewed biomedical journals

Abstract: OBJECTIVE:We undertook this investigation to characterize conflict of interest (COI) policies of biomedical journals with respect to authors, peer-reviewers, and editors, and to ascertain what information about COI disclosures is publicly available. METHODS:We performed a cross-sectional survey of a convenience sample of 135 editors of peer-reviewed biomedical journals that publish original research. We chose an international selection of general and specialty medical journals that publish in English. Selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
0
33

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 15 publications
5
88
0
33
Order By: Relevance
“…In fact, it has been determined that of journals that require conflict of interest disclosures by authors, greater than 50% do not currently require editors or reviewers to disclose financial or other conflicts of interest (3). With two of the major publishers of scientific journals, Elsevier and Blackwell Publishing, and the HHS Office of Research of Integrity having offered suggested guidelines for ethical conduct in the peer review process (4-6), it is staggering that this number of peer-reviewed journals has been slow to adopt a standardized, written policy of ethics governing editors, reviewers and authors alike.…”
mentioning
confidence: 99%
“…In fact, it has been determined that of journals that require conflict of interest disclosures by authors, greater than 50% do not currently require editors or reviewers to disclose financial or other conflicts of interest (3). With two of the major publishers of scientific journals, Elsevier and Blackwell Publishing, and the HHS Office of Research of Integrity having offered suggested guidelines for ethical conduct in the peer review process (4-6), it is staggering that this number of peer-reviewed journals has been slow to adopt a standardized, written policy of ethics governing editors, reviewers and authors alike.…”
mentioning
confidence: 99%
“…Only 3% of respondents published COI disclosures of peer reviewers and 12% published editors' COI disclosures, while 11% and 24%, respectively, reported that this information was available upon request. In this survey, estimates were directly provided by the corresponding editors but no information was taken directly from the actual publications 7 .…”
Section: Coi -Conflicts Of Interest; Icmje -International Committee Mmentioning
confidence: 99%
“…Therefore, COI should be made clear to the readers to facilitate their own judgement and interpretation of their relevance and potential implications. Authors are responsible for fully disclosing potential COI [6][7][8][9][10] . Failure to do so has shaken the confidence of the public, health professionals and scientists in the peerreviewed medical literature [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations